Cloning and expression of the pkg1 gene from the GH55 family of the mycoparasite Pestalotiopsis kenyana PG52 - Yan, Mengling; Sui, Wenjing; Chen, Chen; Gao, Ruotian; Li, Jinqiu; Li, Jing (Frontiers in Microbiology, 2025)
Introductionβ-1,3-glucanases are involved in degrading the cell wall of phytopathogenic fungi and can be used to control plant diseases. Our research group previously predicted that Pestalotiopsis kenyana PG52 has more glycoside hydrolase 55 (GH55) family genes than Pestalotiopsis sp. CR013. Therefore, their identification and expression were analyzed to screen the glucanase genes that may be involved in mycoparasitism.MethodsUsing bioinformatics methods, the GH55 gene family was identified and predicted in the PG52 strain. According to the expression level of the gene induced by aeciospores, the GH55 family gene pkg1, which may be involved in mycoparasitism, was screened for cloning and expression. The expressed protein was purified, and its activity and ability to destroy aeciospores were determined.ResultsThere were seven GH55 family genes from the PG52 genome. An endo-β-1,3-glucanase gene, pkg1, which may have a mycoparasitic effect, was identified. The pkg1 gene was 2,304 bp long and expressed a stable 784 amino acid (aa) extracellular protein in Escherichia coli Rosetta (DE3). The enzyme activity of PKG1 was 4.88 U/mL, with laminarin as the substrate. The optimum temperature for PKG1 was approximately 60 °C, while the highest activity was at pH 7.0 ~ 9.0, and it exhibited destructive activity against aeciospore walls.DiscussionThe β-1,3-glucanase gene from P. kenyana was successfully cloned and showed activity against aeciospores, which highlights its probable role in the mycoparasitic activity of P. kenyana, suggesting a new source of enzymes for biological control strategies that target fungal cell walls.